2022
DOI: 10.1088/2515-7620/ac5e0a
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of decreasing diurnal temperature range in eastern Northern Hemisphere

Abstract: As a key variable in the climate system, the diurnal temperature range (DTR) has received a lot of attention in the atmospheric science community. The majority of published papers interpret DTR change in terms of variables like water vapor, cloud cover, and enhanced vegetation index. In this study, we found that the DTR has an obvious decreasing trend in the semi-arid Northeastern Hemisphere, and the decreasing trend is mainly caused by the continuous release of CO2 closely associated with a drying process in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The zonal average trends show decreasing DTR trend over the North Hemisphere, while it increased over the Southern Hemisphere. This is consistent with Guan et al (2022) who reported a decreasing DTR trend over the Northern Hemisphere between 1902 and 2011. They reported a decrease in DTR across the aridity gradient over the Northern Hemisphere, but positive trend was observed in the dry region of the northwestern hemisphere, which agrees with the results presented in this study.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The zonal average trends show decreasing DTR trend over the North Hemisphere, while it increased over the Southern Hemisphere. This is consistent with Guan et al (2022) who reported a decreasing DTR trend over the Northern Hemisphere between 1902 and 2011. They reported a decrease in DTR across the aridity gradient over the Northern Hemisphere, but positive trend was observed in the dry region of the northwestern hemisphere, which agrees with the results presented in this study.…”
Section: Resultssupporting
confidence: 93%
“…The lower increase in night-time warming and insignificant change in the long-term trend of soil moisture (Figure S2) raises the question of how these may impact the coupled processes of carbon assimilation and loss in the drylands. Drying conditions in the dry areas of the northeastern hemisphere is suggested to have impacted the differential warming of the region (Guan et al, 2022) due to an increase in the carbon release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymmetrical changes in maximum and minimum air temperatures lead to a mosaic of either downward or upward trends in DTR depending on the region/site, suggesting topographical and geographical variabilities, although there are cities with no significant trend. Most previous studies have shown a decrease in global DTR over recent decades [19][20][21]59], while some other studies that focus on specific regions have reported increasing trends in DTR [23,[30][31][32][33]60]. In Spain, for example, the maximum air temperature has increased at a higher rate than the minimum air temperature since 1961 [33], and in the Baltic region, an increasing trend in DTR depending on the season has also been reported [23].…”
Section: Discussionmentioning
confidence: 96%
“…Both of them show strong linkages with human health, vegetation, crop yields, and physical infrastructure (Fontana et al, 2015;Zuo et al, 2015;Ramamurthy et al, 2017;Shiflett et al, 2017;Yuan et al, 2019). In spite of overall trend toward warmer temperatures (Franzke, 2015), numerous studies revealed that nighttime minimum temperatures increased at a faster rate than the daytime maximum temperatures, resulting in a decrease in the diurnal temperature range on global scale and regional scale (Gan et al, 2019;Guan et al, 2022). Specifically, Tmin has been increasing roughly twice as fast as Tmax since 1950 in most parts of the world (Vose et al, 2005).…”
Section: Introductionmentioning
confidence: 99%